'The Sinewes of Truth': Binding Law and Emotion in Thomas Tomkis's Lingua. (14th December 2017) - Johnson, Toria
Abstract: This essay traces the intersections of truth, law and emotion in Thomas Tomkis's 1606 play Lingua : Or the Combat of the Tongue and the Five Senses for Superiority, in which the title character appeals for full status as a Sense. Moments of judgment structure the play, and suggest an overarching effort to seek truth in spite of the muddiness introduced by deceitful senses and heightened emotion. Although the bulk of the play emphasizes the volatility of the Five Senses, their susceptibility to emotion, and the unreliability of the 'truths' they report, it is Lingua who is ultimately 'contained' by the play's legal structures. Nonetheless, Tomkis invites us to consider this vision of law's power as little more than a fantasy.